Planning, implementing and evaluating a social and communication skills course for riding instructors - Seefeld, Annika (2016)
Social and emotional skills are very important for effective coaching. As research in this field is still very limited, the purpose of this study was to plan, implement and evaluate a course teaching social and emotional skills to riding instructors. The objective of this research project was to analyse the usefulness and feasibility of a social and communication skills course for riding instructors. The present research study is an educational action research case study approach. The course was based on Thomas Gordon’s Model of Human Relationships and included different skills such as I-Messages, Active Listening, Shifting Gears and Problem Solving Skills. In total four participants took part in the course, varying in age, discipline and employment status. The course was carried out in eight 1 ½ hours sessions on two days in Bielefeld, Germany. The data collection methods were researcher’s notes and researcher’s log. The course was video recorded. For further data collection feedback forms and a knowledge test were filled in by the participants as well as verbal feedback was written down. In addition, all participants send three more feedback forms to the researcher, one after two weeks, another one after one month and the last one after three months. An important finding from the researcher was that the course is applicable for everybody regardless of their previous knowledge or skills. Every participant is improving, learning and practicing in their own pace. Therefore, it is indispensable for the supervisor of a SEL intervention to be flexible in his or her support and way of teaching. However, a heterogeneous group of participants is an advantage for sharing different experience, support each other and look at problems from a different point of view. In addition it was shown that the progress of the course needs to be traced and changes need to be made according to new information gained through the analysis. All participants agreed that skills learned during the course are useful for their work and for effective communication. However, it was shown that all participants struggled to apply the skills during riding lessons and rather used them in conflict situations with different customers. It was examined that all participants increased their theoretical knowledge of social and communication skills. Furthermore, all participants agreed that the course raised awareness of the importance of effective communication. For future research in this field it is recommended to support participants also at work to apply the newly learned skills. However, more research is needed to examine the long-term effect as well as applicableness.